Circulating microparticles are prognostic biomarkers in advanced non-small cell lung cancer patients - Wang, Chin-Chou (Oncotarget, 2017)
We investigated whether circulating microparticles (MPs) could serve as prognostic biomarkers in non-small cell lung cancer (NSCLC) patients. We enrolled 25 control subjects and 136 NSCLC patients categorized into disease-progression (DP, n=42) and disease-control (DC, n=94) groups. Flow cytometric analysis showed that levels of four types of circulating microparticles (EDAc-MPs, EDAp-MPs, PDAc-MPs and PDAp-MPs) were higher in the study patients than the control subjects (P < 0.04). DP patients showed poor initially performance status and more non-adenocarcinomas than DC patients. DC patients showed more EGFR mutations and poorer performance to targeted therapy than DP patients (P < 0.01). Three months after therapy, the levels of all four types of circulating MPs were lower in DC than DP patients (P < 0.02), and were comparable to the levels in control subjects. In addition, the levels of circulating MPs after 3 months accurately predicted one-year prognostic outcomes (P < 0.05). This study showed that circulating MPs are valuable prognostic biomarkers in advanced NSCLC patients.